2004
DOI: 10.1103/physrevc.69.034335
|View full text |Cite
|
Sign up to set email alerts
|

New effective interaction forpf-shell nuclei and its implications for the stability of theN=Z=28closed core

Abstract: The effective interaction GXPF1 for shell-model calculations in the full pf shell is tested in detail from various viewpoints such as binding energies, electro-magnetic moments and transitions, and excitation spectra. The semi-magic structure is successfully described for N or Z = 28 nuclei, 53 Mn, 54 Fe, 55 Co and 56,57,58,59 Ni, suggesting the existence of significant core-excitations in low-lying nonyrast states as well as in high-spin yrast states. The results of N = Z odd-odd nuclei, 54 Co and 58 Cu, als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
570
3
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(622 citation statements)
references
References 69 publications
45
570
3
4
Order By: Relevance
“…First two columns show old and new experimental data, see [6] for details. Next three columns collect the results of shell-model calculations using MSDI3 [13], GXPF1 [14], and GXPF1A [15] interactions, respectively. Last column shows the results obtained in this work using six reference Slater determinants described in the text.…”
Section: No-core Configuration-interaction Calculations For 0 + Statementioning
confidence: 99%
“…First two columns show old and new experimental data, see [6] for details. Next three columns collect the results of shell-model calculations using MSDI3 [13], GXPF1 [14], and GXPF1A [15] interactions, respectively. Last column shows the results obtained in this work using six reference Slater determinants described in the text.…”
Section: No-core Configuration-interaction Calculations For 0 + Statementioning
confidence: 99%
“…However, it has been shown that this core is rather soft and only a very limited description is provided by the closed-shell model for the magic number 28 [4]. These structures were successfully described for N or Z = 28 nuclei only after considering the existence of significant core-excitations in low-lying non-yrast states as well as in high-spin yrast states [3].…”
Section: Introductionmentioning
confidence: 99%
“…We have used the model space and the residual interaction named GXPF1, developed for the description of fp-nuclei [3,18]. The calculation with the GXPF1 interaction was performed in the full fp shell with up to eight particle excitations from the 1f 7/2 orbital to the 1p 3/2 , 1f 5/2 and 1p 1/2 orbitals.…”
Section: Shell Model Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are compared to Shell Model calculations using the GXPF1 effective interaction, developed for use in the fp shell. The πf −1 7/2 ⊗ν(p 2 3/2 f 1 5/2 ) configuration was assigned to the yrast levels.Nuclei close to doubly magic shell closures are the object of extensive experimental and theoretical investigations [1][2][3]. Spectroscopic data from these nuclei provide essential information for the parameter sets of spherical shell-model calculations.…”
mentioning
confidence: 99%